2006 International Conference on Machine Learning and Cybernetics 2006
DOI: 10.1109/icmlc.2006.258846
|View full text |Cite
|
Sign up to set email alerts
|

A Vendor-Buyer Stochastic Inventory Model with Lead Time Reduction in Supply Chain

Abstract: Time-based competition strategy embodies lead time reduction (LTR) at operational level in supply chain. When supply chain channel puts LTR into practice, there exist two questions: how LTR to effect on profit of supply chain actors and if LTR may not make both supply actors better off, how to coordinate the supply channel? A single shorter-life-cycle product model of the supplier-retailer decentralized decision-making supply chain is proposed in this paper. On the assumption that the mean demand is constant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Heydari Kazemzadeh and Chaharsooghi 8 found that increase in variations in LT can cause BWE but if these variations are uniform throughout the SC then there would be no impact on BWE. Song and Ming 21 found that profit of an SC is a decaying function of LT. Yina, Xuejun and Fei 28 found that by crashing the LT an extra cost is encountered; hence, the inventory should be optimized by controlling the LT optimally. The authors also proposed an inventory optimization model.…”
Section: Introduction and Origin Of Bullwhip Effectmentioning
confidence: 99%
“…Heydari Kazemzadeh and Chaharsooghi 8 found that increase in variations in LT can cause BWE but if these variations are uniform throughout the SC then there would be no impact on BWE. Song and Ming 21 found that profit of an SC is a decaying function of LT. Yina, Xuejun and Fei 28 found that by crashing the LT an extra cost is encountered; hence, the inventory should be optimized by controlling the LT optimally. The authors also proposed an inventory optimization model.…”
Section: Introduction and Origin Of Bullwhip Effectmentioning
confidence: 99%